Exploring older adults' intergenerational friendships: from homophily to an all-age identity - ELLIOTT O'DARE, CATHERINE (Trinity College Dublin. School of Social Work & Social Policy. Discipline of Social Studies, 2019)
Intergenerational friendship is a friendship between a chronologically old and a significantly younger adult. Influenced by the principle of homophily ('birds of a feather flock together'), research has predominately focused on peer-aged friendships among older or younger adults. This approach reflects a social construction of older adults as unsuited to forming naturally occurring, equal, mutually enjoyable friendships with younger non-kin adults (Elliott O'Dare et al., 2017). By focusing on the 'older friend', this thesis aims to understand the role intergenerational friendships play in how older persons experience older age and friendship in later life. This study took a qualitative approach using Constructivist Grounded Theory to generate theoretically informative data (Charmaz, 2014). Twenty-three people aged 65 and over were interviewed in Ireland to attain rich co-constructed talk data, and observational memos were used to capture data - 'props' and 'prompts' - in participants' homes and environs. Three key concepts emerged from the research. First, age homophily is challenged with a new conceptualisation of homophily of doing-and-being. Second, participants signalled a process of maintaining and deploying an all-age identity through intergenerational friendship. Age was presented as a fluid spectrum of performance. Third, continuity in belonging and connectedness through intergenerational friendships was an essential part of embracing a good old age. In the everyday - in friendship - compliance with and resistance to social and cultural age stereotyping and ageism was enacted. The accounts of exclusion and inclusion, homophily of doing-and-being, celebrating difference and age difference, and holding an all-age identity all formed part of the participants' lived experience of older age and intergenerational friendship. Being an older intergenerational friend was imbued with seeking joy, belonging and connectedness in everyday life.
APPROVED
Keywords: Intergenerational friendship; older adults; stereotyping; homophily; friendship; ageism